Study of inundation and eco drainage system approach in Cicayur Kampong area - Aurice Pradiesha Alivia; Yureana Wijayanti; Ayu Kusumadewi Riana (E3S Web of Conferences, 2023)
Cicayur Kampong, Pagedangan District, Tangerang Regency is a residential area adjacent to the urban area. This area has experienced inundation since 2018. This study aims to evaluate existing drainage systems, assess the performance of channels in serving surface runoff to their catchment areas and provide alternative solutions by eco drainage approach using rainwater harvesting and recharge well. This study was carried out by processing daily rainfall data over a time span of 2011 to 2021. Hydrology analysis was performed manually, and the hydraulic simulation was conducted using the Storm Water Management Model (SWMM) 5.1. The rainfall intensity applied for modeling is 37.29 mm/hour, 46.96 mm/hour, and 53.41 mm/hour for 2, 5, and 10 years return periods, respectively. The results of the simulation of the existing drainage system show that there are 2 (two) channels that experience overflow during the 2 and 5-year return periods and increase to 5 (five) channels during the 10-year periods. Alternative solution with rainwater harvesting and recharge well shows a large reduction in surface runoff flowing into drainage channels by 45%.